Metabolite Profiles of the Green Beans of Indonesian Arabica Coffee Varieties - Nizar Happyana; Amelinda Pratiwi; Euis Holisotan Hakim (International Journal of Food Science)
The green beans of 3 Indonesian arabica coffee varieties, namely, ateng, buhun, and sigararutang, were analyzed with 1H NMR-based metabolomics coupled with alpha-glucosidase inhibitory activity assay. These coffees were cultivated in the same geographical conditions. The PLSDA model successfully classified the green coffee beans based on their varieties. To reveal the characteristic metabolites for each coffee variety, S-plot of two-class OPLSDA models was generated and analyzed. Ateng coffee was characterized with trigonelline, sucrose, 5-CQA, and acetic acid. The characteristic metabolites of buhun coffee were citric acid and malic acid. Meanwhile, the most discriminant compound of sigararutang coffee was quinic acid. HCA analysis revealed the lineage relationship of the 3 coffee varieties. Ateng coffee had closer lineage relationship to sigararutang compared to the buhun coffee. Alpha-glucosidase inhibitory activity of the coffee samples did not differ widely. IC50 values of alpha-glucosidase inhibitory activity of ateng, sigararutang, and buhun coffees were 3.01±0.16, 3.14±0.20, and 5.05±0.28 mg/mL, respectively. Although grown in the same geographical conditions, our results revealed that each coffee variety possessed a unique metabolome clarifying the diversity of Indonesian arabica coffees. This study verified that 1H NMR-based metabolomics is an excellence method for discovering the lineage relationship in the samples with different varieties or cultivars.